Phosphorus Dynamics under Saline Water Irrigation and Phosphorus Fertilization in Cowpea: Phosphorus transformation under saline irrigated cowpea cultivated soil - Jat, Pooja Devi; Kumawat, Chiranjeev; Sharma, K. K.; Dadhich, S. K.; Kumawat, Arvind; Verma, Rajhans; Yadav, Manish (Journal of Soil Salinity and Water Quality, 2025)
Soil salinity is one of the major problems in arid and semi-arid areas around the world. Salinity results in soil and water degradation. Cowpea is very sensitive to salinity and sodicity as compared to cereals and oilseed crops. Salinity reduced germination percentage and germination index. In saline soils, availability of phosphorus is low due to immobilization of applied P, fixation of P by Ca. The requirement of phosphorus for pulses is more important than nitrogen and potassium but the availability of phosphorus is low in Rajasthan. The experiment consisted of twelve treatment combinations including three levels of saline irrigation water [normal (1.26) and 6 dS m-1 keeping Cl-: SO42- ratio in 3:1 and 1:3] and four levels of phosphorus application (0, 10, 20 and 30 mg kg-1). The experiment was conducted in pots and carried out in completely randomized design (CRD) with three replications. Phosphorus transformation in soil, yield attributes and yield of the crop were observed significantly higher with normal (1.26 dS m-1) irrigation water and 30 mg kg-1 phosphorus application in soil. The result indicated that irrigation with normal (1.26 dS m-1) water and 30 mg kg-1 phosphorus application in soil to the cowpea crop significantly increased the different forms of soil phosphorus viz., Al-P, Fe-P, saloid-P, organic-P and total-P, effective number of nodules per plant, nodule index, fresh and dry weight of nodules, plant height, pods per plant, seeds per pod, seed index, seed and straw yield.